2021
DOI: 10.1111/jcal.12553
|View full text |Cite
|
Sign up to set email alerts
|

The role of digital informal learning in the relationship between students' digital competence and academic engagement during the COVID‐19 pandemic

Abstract: During the COVID‐19 crisis, digital informal learning is important for students' academic engagement. Although scholars have highlighted the importance of students' digital competence in improving digital informal learning (DIL), the mediating role of DIL between digital competence and academic engagement has remained ambiguous. The purpose of this study is to investigate the relationship between students' digital competence and their academic engagement with the mediating role of DIL in the higher education c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 60 publications
(119 reference statements)
3
42
0
3
Order By: Relevance
“…Digital competence is not only the basis for the use of digital technologies, but can also link to various required literacy for students. Students with higher digital competence can have better academic engagement and study enthusiasm, which are major concerns among world-wide universities and higher education institutions [10][11][12]. The development of digital competence needs to be perceived as part of lifelong learning [13].…”
Section: Introductionmentioning
confidence: 99%
“…Digital competence is not only the basis for the use of digital technologies, but can also link to various required literacy for students. Students with higher digital competence can have better academic engagement and study enthusiasm, which are major concerns among world-wide universities and higher education institutions [10][11][12]. The development of digital competence needs to be perceived as part of lifelong learning [13].…”
Section: Introductionmentioning
confidence: 99%
“…Greater motivation and time management skills, crucial in remote learning environments, have been linked to increased academic performance [22]. Additionally, the students' digital competencies are significantly correlated with their academic engagement [23], what can cause inequalities in their performance due to a lack of these skills.…”
Section: Learning Strategies and Student Profilesmentioning
confidence: 99%
“…Digital competence was broadly described by Heidari et al [ 11 ] as “the skill of using digital technologies effectively and the ability to critically analyse online information”. It has so far been studied through several frameworks; one proposed by Calvani et al [ 12 , 13 ] includes three dimensions: technical skill (comprising visual literacy, an understanding of technological concepts, and operative knowledge to solve common technological problems); cognitive skill (including high-order cognitive skills allowing the user to interpret, evaluate, and organise the data); and ethical knowledge (concerning the ability of the user to interact with others via digital media and the effects of those interactions on their sense of online responsibility and citizenship) [ 11 ].…”
Section: Digital Competencementioning
confidence: 99%
“…Another study of Iran-based university students during the COVID-19 pandemic [ 11 ] found that digital competence was positively correlated not only with academic engagement but also with informal digital learning, described as self-controlled, self-directed learning that is not usually classroom-based or directed through formal educational institutions. The importance of digital competence to allow uptake of digital technologies in nursing education was further described by Meum et al [ 27 ] in a qualitative study, which highlighted the benefits of using digital educational platforms.…”
Section: How Digital Competence Affects Cme Uptakementioning
confidence: 99%